Segmentation of planar surfaces from range data - Son, Ik Soo. (2009)
This project is the first part of a long term project that aims to develop a complete three-dimensional object recognition system from range data for industrial applications. The objective of this project is to develop a robust algorithm to extract all the planar surfaces from range data using region growing technique controlled by least-square criterion to accomplish the task of segmentation. This project will therefore form the foundation for further improvement for extracting of higher order surfaces, three-dimensional feature representation and ultimately object recognition. The planar surface segmentation algorithm is then to be tested by using both synthetic data and experimental data for evaluation.